Is monetary financing inflationary? A case study of the Canadian economy, 1935 - 75 - Josh Ryan-Collins (Levy Economics Institute of Bard College, 2015)
Historically high levels of private and public debt coupled with already very low short-term interest rates appear to limit the options for stimulative monetary policy in many advanced economies today. One option that has not yet been considered is monetary financing by central banks to boost demand and/or relieve debt burdens. We find little empirical evidence to support the standard objection to such policies: that they will lead to uncontrollable inflation. Theoretical models of inflationary monetary financing rest upon inaccurate conceptions of the modern endogenous money creation process. This paper presents a counter-example in the activities of the Bank of Canada during the period 1935-75, when, working with the government, it engaged in significant direct or indirect monetary financing to support fiscal expansion, economic growth, and industrialization. An institutional case study of the period, complemented by a general-to-specific econometric analysis, finds no support for a relationship between monetary financing and inflation. The findings lend support to recent calls for explicit monetary financing to boost highly indebted economies and a more general rethink of the dominant New Macroeconomic Consensus policy framework that prohibits monetary financing.
Keywords: B22; B25; E02; E12; E14; E31; E42; E51; E52; E58; E63; N12; N22; O43; 330; Monetary Policy; Monetary Financing; Inflation; Central Bank Independence; Fiscal Policy; Debt; Credit Creation